Genetic and Non-genetic Factors Affecting Gestation Length and Calve Birth Weight of Sahiwal-Friesian Crossbred Groups - Talukder, MAI; Panandam, JM (The Agriculturists, 2010)
This study focused on the dairy unit at the Ladang Pusat Ternakan Haiwan Ayer Hitam in Johor, Malaysia. Eight crossbreed groups namely M50, M50-1, M50-2, M50-3, M56, M63, M75 and M75-1 were evaluated. Retrospective data on gestation length and calf birth weight were extracted for evaluation of 1346 animals and were analyzed between 1981 and 2001. Effects of breed group, parity, calf sex and age at calving were non significant for GL. Year of birth was only significant (P<0.05) affected for GL. The GL for the breed groups ranged between 279 - 283 days. The cow breed group x parity interaction effect was significant (P<0.05) for CBW. Sire breed group, calf sex and age at calving significantly (P<0.05) affected the CBW. There was no significant difference in CBW of the cow breed groups for the first two parities. M50, M50-1, M63 and M75-1 had significantly (P<0.05) higher CBW in the third and fourth parity (26.76-28.98 kg). M50-3 and M56 had significantly (P<0.05) lower CBW than M50 and M63. M56 had the lowest (P<0.05) CBW in the fourth parity (22.22 ± 1.24 kg). Individual additive genetic effect, maternal additive genetic effect, individual heterosis and maternal heterosis were non-significant for GL and CBW. Calf sex significantly (P<0.01) affected the CBW in all breed groups except M56 and M63. Male calves weighed significantly (P<0.01) heavier than female calves in the earlier breed group. Calf mortality ranged between 3.49 - 7.27%. The highest calf mortality at birth was observed in M75 (7.27%) followed by M50-3 (6.8%) and M75-1 (5.66%). The lowest mortality was observed in M50-1. M50, M50-1, M63 and M75-1 had better performance on CBW. Higher Friesian grades calf mortality rate was higher than lower Friesian grades. The non genetic factor year of birth only affected GL, but most of the genetic and non genetic factors significantly (P<0.05) affected the CBW.